Developing Production Planning and Control System by Applying Dispatching Rules: A Case Study at A Packaging Manufacturer - Brahmantyo, Fransiskus Xaverius Dimas Adrian; Kurniawan, Ivan; Saraswati, Triarti (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
Production planning and control (PPIC) is a critical element in manufacturing process. PPIC consists of a lot of activities which lead complexity within its system. Problems such as amount of safety stock, parts inventory, and production scheduling commonly occurs within manufacturing process. A need of efficient PPIC system become an important factor in smoothing the production process which affect company’s profitability and sustainability. This research provides production planning and control system which developed based on implementation of pull system, optimal safety stock calculation, and dispatching rules for the sequencing of the production scheduling. A case study in a packaging manufacturer is provided for testing the proposed system. A comparison analysis is conducted and it consists of the safety stock calculation, parts inventory on hand, and the economic analysis. From the improvements, positive results are obtained. The accumulation of final parts inventory and average daily parts inventory are reduced up to 38%. Safety stock of sub-product reduced up to 82% and the safety stock of holding cost are reduced by 77%.